2017
DOI: 10.1038/s41598-017-09828-4
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of remote diabetic foot ulcer assessment using mobile phone images

Abstract: Despite their potential for telemedicine in diabetic foot ulcer treatment, diagnostic accuracy of assessment of diabetic foot ulcers using mobile phone images is unknown. Our aim was to determine the validity and reliability of remote diabetic foot ulcer assessment using mobile phone images. Fifty diabetic foot ulcers were assessed live and photographed. Five independent observers remotely assessed the mobile phone images twice for presence of nine clinical characteristics and three treatment decisions. Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 35 publications
0
55
0
9
Order By: Relevance
“…At the same time, however, sharing information with clinicians creates challenges in terms of information ownership, security and privacy [36]. It also raises the question of accuracy, with previous studies highlighting that mobile phone images of DFUs in isolation may not be sufficient for clinicians to make reliable diagnosis [37]. Furthermore, it would also require a change in organizational practices, where clinicians receive time and remuneration for reviewing such information without the patient present.…”
Section: Principal Resultsmentioning
confidence: 99%
“…At the same time, however, sharing information with clinicians creates challenges in terms of information ownership, security and privacy [36]. It also raises the question of accuracy, with previous studies highlighting that mobile phone images of DFUs in isolation may not be sufficient for clinicians to make reliable diagnosis [37]. Furthermore, it would also require a change in organizational practices, where clinicians receive time and remuneration for reviewing such information without the patient present.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Using support vector machines, they could determine the wound boundaries even more accurately . Van Netten et al found that assessment of diabetic foot ulcers using a mobile phone compared to live assessment (as reference), gave strong support for the decision for per‐wound debridement, but low interobserver reliability [kappa ( k ) = 0.09 ‐ 0.49] and a moderate intra‐observer reliability ( k = 0.47 ‐ 0.64) for assessing the presence of ischemia, infection, granulation, slough, tracking or tunneling, moist or an exuding wound, cellulitis, or erythema …”
Section: Resultsmentioning
confidence: 99%
“…More recently, Van Netten et al concluded that there was a low interobserver and moderate intraobserver reliability in the diagnosis of a variety of diabetic foot problems based on mobile phone images . Overall, these findings suggest that digital (mobile phone) images have applicability in some areas of assessment of pre‐signs of ulceration, but are limited in use in others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations